STRUKTUR KOMUNITAS GASTROPODA (MOLUSKA) DI PERAIRAN BENDUNGAN MENAMING KABUPATEN ROKAN HULU RIAU - Wahyuni, Sri; Yolanda, Rofiza; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about structure of Gastropod communities in the Menaming dam Rambah district Rokan Hulu regency provice was conducted in July to December 2014 with survey method, the sample sampling technique is purposive sampling. Samples were collected using eckman dredge with 9 repetitions at each station that has been determined. The results showed three family 5 species, abundance 1022,22 indvidual / m2, diversity 0,81, uniformity of 0.56, dominance 0,61. Some of the environmental factors that affect the strukture community Gastropods are temperature, pH, Brightness, TSS, DO, and substrate. Substrate is a physical factor which greatly affects the water chemistry where Gastropods.